2021
DOI: 10.1080/01426397.2020.1867713
|View full text |Cite
|
Sign up to set email alerts
|

Explaining landscape preference heterogeneity using machine learning-based survey analysis

Abstract: We conducted a national survey on a high-quality internet panel to study landscape preferences in Norway, using photos as stimuli. We examined preference heterogeneity with respect to socio-demographic characteristics and latent topics brought up by the respondents, using ordinal logistic regression and structural topic modelling (STM), a machine learning-based analysis. We found that pasture landscapes are the most favoured (55%), while densely planted spruce forests are the least favoured (8%). The contrast … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 39 publications
2
10
0
Order By: Relevance
“…Gatersleben and Andrews [9] found that natural environments with a higher level of prospect (clear field of vision) and lower level of refuge are more restorative than environments with a lower prospect and high refuge. The positive impact of an open view has been corroborated by yet other authors, e.g., [12,13,24]. Their findings imply that less permeable and potentially dangerous environments demand more attention, lead to a lower restorative potential, and may be, therefore, less preferred.…”
Section: Environmental Preferences and Post-mining Forestsmentioning
confidence: 60%
See 3 more Smart Citations
“…Gatersleben and Andrews [9] found that natural environments with a higher level of prospect (clear field of vision) and lower level of refuge are more restorative than environments with a lower prospect and high refuge. The positive impact of an open view has been corroborated by yet other authors, e.g., [12,13,24]. Their findings imply that less permeable and potentially dangerous environments demand more attention, lead to a lower restorative potential, and may be, therefore, less preferred.…”
Section: Environmental Preferences and Post-mining Forestsmentioning
confidence: 60%
“…For example, the volume of large trees increases the preference for the forest more in men than in women [22]. Older women in Norway preferred grassland and heathland (compared to forests) more than other population groups [24]. Ribe [25] shows that people favoring resource production have lower standards of visual quality/scenic beauty than people favoring resource protection.…”
Section: Environmental Preferences and Post-mining Forestsmentioning
confidence: 99%
See 2 more Smart Citations
“…Major topics detected include value for money, baggage policy, delays and refund policy. Liu et al ( 2021 ) used STM to analyze responses to 1452 open-ended questions in a survey examining landscape preferences in Norway. Results revealed that consumer choices were driven mainly by themes such as landscape openness, concerns regarding deforestation, biodiversity issues and aesthetic properties.…”
Section: Related Workmentioning
confidence: 99%